Pamphalea tenuissima (Nassauvieae, Asteraceae), a new species from southern Brazil - Trujillo, Cristina; Bonifacino, José M.; Pasini, Eduardo (Phytotaxa, 2019)
Pamphalea tenuissima (Asteraceae), a new species from southern Brazil, is described. The new species is characterized by its finely dissected leaves, herbaceous texture and decumbent habit in most, if not all, of its stems. A detailed morphological description, illustrations, images and a distribution map, ecological preferences and phenology are provided.